Práticas de mapeamento com as tecnologias digitais: para pensar a educação cartográfica na contemporaneidade - Canto, Tânia Seneme do [UNESP] (2014)
With the need of rethinking contemporary educative practices using maps, the present work had as its goal to investigate how new technologies participate on mappings and geographies which emerges from mapping practices developed by young students who are attending to a graduate program for geography teachers. For that, during the research, two cartographic activities experiences were proposed trying to explore with those subjects new characteristics that rose on maps through digital technologies. Based on a new theoretical perspective which conceives map as process and practice, we understand that those interactions made by future teachers during the activities experiences were able to indicate new paths that cartography may take within classroom interfacing technologies